Companies Participation in Developing Sustainability in Local Communities: a Literature Review - Franco, Luciane Silva (2020)
Corporate social responsibility (CSR) in recent years has received significant interest from several researchers who have revealed the results of CSR disclosure in relation to organizational performance around the world. The purpose of our study was to assess the engagement of organizations and the impact on the development sustainability in local community. However, we performed a systematic review applying the Methodi Ordinatio, using the Scopus and Web of Science databases, which resulted in the complete analysis of 28 articles. Among the results obtained, the importance of the relationship between organization and stakeholders, especially community involvement, is emphasized. Evaluation using the stakeholder approach will not only create a holistic assessment of the process, but will also help promote a sense of ownership of the community engagement program. We conclude that business-community engagement brings benefits to both parties and contributes to community development. Keywords: stakeholders, sustainability, community, engagement.